Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw Pada Materi Sistem Pernapasan Yang Terintegrasi Al-Qur’an Surah Al-An’am Terhadap Hasil Belajar - Sri Agusna; Kartika Manalu (Symbiotic: Journal of Biological Education and Science, 2022)
ABSTRACT This study aims to determine the effect of the jigsaw type cooperative learning example on student learning outcomes in the integrated respiratory system material Al-Qur’an Surah Al-An’am in class VIII MTs.S PPM Babussalam. The population in this study means all students of class VIII, totaling 108 students. The sample used was class, totaling27 students and class VIII-3 being the experimental class, totaling 27 students. Data analysis was performed using t test. What will happen is the analysis of the t-count value of 4.425> the t-table value of 2.006 which gives the effect of student learning outcomes using the jigsaw type cooperative learning example on the learning outcomes of class VIII MTs.S PPM Babussalam student. The post test result of students in the experimental class have a big effect. Holistically, students answers include good criteria.